Globular glial tauopathy Type I presenting with behavioral variant frontotemporal dementia. Issue 5 (21st July 2020) - Hirano, Mitsuaki; Iritani, Shuji; Fujishiro, Hiroshige; Torii, Youta; Kawashima, Kunihiro; Sekiguchi, Hirotaka; Habuchi, Chikako; Yamada, Kentaro; Ikeda, Toshimasa; Hasegawa, Masato; Ikeuchi, Takeshi; Yoshida, Mari; et al.
Abstract : Globular glial tauopathy (GGT) is a recently proposed tauopathy characterized by the globular accumulation of four‐repeat (4R) tau in the oligodendroglia (globular oligodendroglial inclusion (GOI)) and astrocytes (globular astrocytic inclusion (GAI)), in addition to deposition in neurons. Although it is proposed that GGT should be classified into three different neuropathological subtypes, previous reports have indicated that subclassification might be difficult in some cases. We report an autopy case of a 79‐year‐old man with behavioral variant frontotemporal dementia (bvFTD). He developed behavioral changes at 67 years of age and had auditory hallucinations and persecutory delusions at admission to a psychiatric hospital at 69 years of age. Neuropathologically, marked atrophy of the frontotemporal lobes and severe degeneration of the white matter and frontopontine tract were observed. The present case corresponded to GGT Type I, as numerous GOIs were observed, predominantly in the frontotemporal region. However, concurrent degeneration of the motor cortex and corticospinal tract suggest characteristics of Type II. Although the relationship between psychotic symptoms and GGT remains unclear, the present case demonstrates heterogeneity of GGT subtypes.